2017
DOI: 10.1007/s00520-017-3964-5
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators of exercise experienced by cancer survivors: a mixed methods systematic review

Abstract: Treatment-related side effects, lack of time and fatigue were key barriers to exercise for survivors of varied cancer types. Insufficient patient education may contribute to the belief that exercise is not helpful when experiencing side effects of treatment, including fatigue. Identifying barriers and facilitators leads to improved support and education from health professionals which is required to provide safe and effective exercise recommendations for survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
189
4
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(222 citation statements)
references
References 73 publications
21
189
4
8
Order By: Relevance
“…For example, in a population-based study of older adults with chronic pain, Larsson et al (2016) found that low kinesiophobia (fear of movement) at baseline predicted higher physical activity levels at the 12-month follow-up [23]. Despite PA being a recommended intervention for cancer pain [6, 7], survivors with pain may be more prone to exhibit fear-avoidance behaviors towards PA and attribute their pain as a challenge to participating in PA [1416, 18, 19]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a population-based study of older adults with chronic pain, Larsson et al (2016) found that low kinesiophobia (fear of movement) at baseline predicted higher physical activity levels at the 12-month follow-up [23]. Despite PA being a recommended intervention for cancer pain [6, 7], survivors with pain may be more prone to exhibit fear-avoidance behaviors towards PA and attribute their pain as a challenge to participating in PA [1416, 18, 19]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous research exploring why cancer survivors are not physically active has identified a variety of barriers to PA, such as cancer treatment-related side effects, pain, fatigue, comorbid medical conditions, time, and motivation [1419]. However, the existing literature examining barriers to PA is largely limited to survivors with breast, prostate, and colorectal cancers [18]. Additionally, most of the studies have been conducted among survivors enrolled in lifestyle and/or exercise intervention clinical trials at academic settings, which may already be biased towards enrolling participants with a prior interest and engagement in PA. Further, a paucity of research has examined exercise barriers in cancer survivors with pain.…”
Section: Introductionmentioning
confidence: 99%
“…From this PA behavior change perspective, taking into account barriers and facilitators to practice is one of the major components [20,[61][62][63]. To date, the main barriers reported in literature differ according to the cancer type, in particular regarding physiological health disorders, even some components seem transverse to all patients: lack of time, geographical location in relation to the hospital center, dif iculty of access to practice.…”
Section: Major Challenges Of Research Perspectives On Pa Survival Anmentioning
confidence: 99%
“…Moreover, there is acknowledgement that "1 size does not fit all" and that restrictive intervention protocols may undermine pragmatism or are misaligned with the preferences and abilities of a given individual. 7,8 This preference may largely be because of convenience 7 and confidence in the qualifications and experience that accompanies guidance and support from QEPs at a Cancer October 1, 2019 cancer center. 5 Assessing effectiveness in exercise-oncology programs remains challenging given their scarcity; however, patient preference data indicate potential design elements that may facilitate participation, satisfaction, and benefit.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews suggest that home-based exercise that is coordinated and supported by qualified exercise professionals (QEPs) at a cancer center are a preference for a majority of cancer survivors. 7,8 This preference may largely be because of convenience 7 and confidence in the qualifications and experience that accompanies guidance and support from QEPs at a Cancer October 1, 2019 cancer center. 9 Moreover, routine monitoring of exercise programing has been shown to support sustained behavior change.…”
Section: Introductionmentioning
confidence: 99%